2016
DOI: 10.1371/journal.pone.0165226
|View full text |Cite
|
Sign up to set email alerts
|

Frontal Lobe Hemodynamic Responses to Painful Stimulation: A Potential Brain Marker of Nociception

Abstract: The purpose of this study was to use functional near-infrared spectroscopy (fNIRS) to examine patterns of both activation and deactivation that occur in the frontal lobe in response to noxious stimuli. The frontal lobe was selected because it has been shown to be activated by noxious stimuli in functional magnetic resonance imaging studies. The brain region is located behind the forehead which is devoid of hair, providing a relative ease of placement for fNIRS probes on this area of the head. Based on function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(77 citation statements)
references
References 32 publications
4
73
0
Order By: Relevance
“…These findings are concordant with the findings reported in our previous papers 6,7 that the hemodynamic response to painful stimuli was stronger than that to nonpainful stimuli and that the response was most strongly present in the medial portion of the aPFC. The overall good test-retest reliability of aPFC response to pain on a single subject provides the basis of employing a prerecorded pain response function to detect subsequent perception of painful events.…”
Section: Summary Of Findings and Potential Clinical Applicationssupporting
confidence: 93%
See 3 more Smart Citations
“…These findings are concordant with the findings reported in our previous papers 6,7 that the hemodynamic response to painful stimuli was stronger than that to nonpainful stimuli and that the response was most strongly present in the medial portion of the aPFC. The overall good test-retest reliability of aPFC response to pain on a single subject provides the basis of employing a prerecorded pain response function to detect subsequent perception of painful events.…”
Section: Summary Of Findings and Potential Clinical Applicationssupporting
confidence: 93%
“…Advantages of putting NIRS optodes on the forehead include the ease of access and the ability to eliminate hair contaminations to obtain a high signal-to-noise ratio. 7 Finally, it should be noted that machinelearning approaches usually require a large sample set to train classifiers to achieve a reasonable sensitivity and specificity. 40 In this fNIRS study, however, we showed that the detection sensitivity of pain response could be significantly improved just by adding a short prerecorded session (a 3-min acquisition containing three noxious stimuli) prior to the actual noxious scan.…”
Section: Comparison Of Our Results With Those From Previous Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The same preprocessing stream was used for experiment 1 and 2. Data preprocessing as well as hemodynamic response function (HRF) estimation was performed using the Windows version of Homer2 68 run in Matlab (R2016b, MathWorks, Inc., Natick, US) and followed a data processing stream used in a recent pain study 69 . In order to convert the raw data into a Homer2-compatible format an adapted version of a freely available Matlab script (by Dr. Dewey https://www.nitrc.org/projects/hitachi2nirs ) was used.…”
Section: Discussionmentioning
confidence: 99%